Heuristic Availability Bias's Effect on Investment Decisions: Moderating Effect of External Locus of Control - IZHAR AHMAD; Muhammad Hamza Haroon (Journal of Business & Tourism, 2024)
In this work, the impact of heuristic availability bias on financial decisions is attempted to be quantified. Besides, the external locus of control as a moderating variable has also been analyzed. The population of the research consists of investors who made investments in the Pakistan Stock Exchange. But 400 responses make up the sample. The responders got questionnaires online. A total of 293 complete replies were received. Moderation and regression analysis of the data were performed. The findings indicate that availability bias greatly affects investors' decision-making process. Later research revealed that locus of control affects both financial responsibilities and availability bias. The government, the State Bank of Pakistan, Pakistan Stock Exchange, and educational institutions all advised giving investors education, protection, and awareness high priority. Better still, they could choose assets that would maximize return.